2022
DOI: 10.1002/sus2.53
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress, mechanisms, and perspectives for crystal and interface chemistry applying to the Zn metal anodes in aqueous zinc‐ion batteries

Abstract: The need for large‐scale electrochemical energy storage devices in the future has spawned several new breeds of batteries in which aqueous zinc ion batteries (AZIBs) have attracted great attention due to their high safety, low cost, and excellent electrochemical performance. In the current research, the dendrite and corrosion caused by aqueous electrolytes are the main problems being studied. However, the research on the zinc metal anode is still in its infancy. We think it really needs to provide clear guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 134 publications
0
32
0
Order By: Relevance
“…Fortunately, the strategies, such as employing the interface modification layer, developing the separator design, and utilizing electrolyte additive and current collector, have been introduced to restrain Zn dendrite successfully. Hydrogen evolution reaction (HER) is another challenge in an aqueous electrolyte. , It has been demonstrated that gel polymer electrolyte (GPE) can significantly inhibit HER; however, Zn dendrite is also induced by uneven Zn plating. …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the strategies, such as employing the interface modification layer, developing the separator design, and utilizing electrolyte additive and current collector, have been introduced to restrain Zn dendrite successfully. Hydrogen evolution reaction (HER) is another challenge in an aqueous electrolyte. , It has been demonstrated that gel polymer electrolyte (GPE) can significantly inhibit HER; however, Zn dendrite is also induced by uneven Zn plating. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It is reported that employing active metals (such as Li, Na, Zn and K) as anodes directly is a hopeful method to significantly enhance the energy density of batteries. [5][6][7][8][9][10][11][12][13][14] Among them, the sodium metal anode (SMA) has attracted great interest benefiting from its high theoretical capacity (1166 mA h g À1 ), low redox potential (À2.71 V vs. standard hydrogen electrode) and cost-effectiveness. [15][16][17][18][19][20] However, the practical application of SMAs is crucially hampered by dendrite growth and ''dead'' Na generation, which are principally derived from the uncontrolled Na deposition, leading to poor Coulombic efficiency, short cycle lifespan and even safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported a modification method for zinc anodes by utilizing a ball-milling clay precipitate (designated as BMC, consisting of the unetched MAX phase and the Ti 3 C 2 T x phase) to construct a three-dimensional (3D) framework on the surface of zinc foil (Zn@BMC) 39 . In addition, some researchers changed the structure of zinc metal by rolling from the problem of zinc metal itself 40 , and adjusted the preferential deposition of zinc crystal plane 17,41 . However, this method is obtained by changing the zinc metal into a molten state at 500 °C, then cooling it to normal temperature, and repeatedly rolling it for 3 cycles to deform it.…”
Section: Introductionmentioning
confidence: 99%
“…35 In addition, some researchers changed the structure of zinc metal by rolling from the problem of zinc metal itself, 41 and adjusted the preferential deposition of zinc crystal plane. 19,42 However, this method was developed by changing the zinc metal into a molten state at 500 °C, then cooling it to normal temperature, and repeatedly rolling it for 3 cycles to deform it. The structure is difficult to commercialize due to the complicated process and high cost.…”
Section: Introductionmentioning
confidence: 99%